METHYL JASMONATE INCREASES ACTIVITIES OF ALDEHYDE OXIDASE AND AUXIN CONTENTS IN MAIZE (Zea mays) - D. Han; Y. Oh; W. J. Park (Journal of Animal and Plant Sciences, 2015)
Methyl jasmonate (MeJA) affects diverse developmental processes, although it has been extensively investigated as a defence hormone.  MeJA likely controls plant development through cooperation with other hormones, especially with auxin. In this study, we found that exogenously applied MeJA increased aldehyde oxidase (AO) activities in the roots and  leaves of maize (Zea mays). In addition, MeJA increased the level of free IAA in leaves, suggesting that MeJA increased the contents of free IAA by regulating AO activities.
Keywords: Aldehyde oxidase; indole-3-acetic acid (IAA); methyl jasmonate; maize (Zea mays)